Ethnic diversity and public policy: An overview - Crawford Young (United Nations Research Institute for Social Development (UNRISD), 1994)
The author argues that cultural pluralism is an enduring attribute of contemporary societies ethnicity will not disappear with modernization, as it was once believed. In addition, ethnic identification should be considered a normal and healthy response to the pressures of the globalizing marketplace. Ethnicity acts as a trigger for violent conflict only when it is mobilized and manipulated to create a sense that one's interests are threatened because of one's ethnicity, or because of the activities of other ethnic groups. The most important policy question for accommodation in ethnically diverse societies, therefore, becomes how to promote an inclusive sense of ethnicity and a loyalty to the larger society as well as to one's own ethnic group. When such a civic identity is successfully established, it makes hate-based mobilization of ethnic groups very difficult. The paper reviews constitutional formulas that have been used in ethnically diverse societies, and examines in particular the strengths and weaknesses of federalism and consociationalism. Different types of electoral systems are also discussed. It is argued that there is a wide range of such systems, and that innovative variations of the one-person-one-vote system have proven successful in a number of settings. The impacts of cultural policies and economic policies on ethnic accommodation are also explored. It is important to foster a sense of national identity through the formal educational system to the extent possible; support for multilingualism can be important in this regard. For national minorities and indigenous peoples, guarantees of cultural autonomy and security, regional self-rule, adequate representation in the central institutions and assurance of language preservation are important for ethnic accommodation. Although, in general, policies that contribute to economic growth help ethnic accommodation because intergroup conflicts over resources become less salient, policies that help the national economy at the expense of one ethnic group have had disastrous consequences. In some situations, policies of ethnic preference have proven successful in alleviating tensions, although such policies have a mixed record. They tend to be more successful where the target groups are clearly defined and do not comprise the majority of the population. The paper concludes with the argument that experience has shown that attempts at "nation building" through ethnic homogenization cannot succeed. Nor can domination on the part of one ethnic group provide long-term stability in a society. The most durable way to accommodate diversity is to create a sense of the nation being a civic community, rooted in values that can be shared by all ethnic components of the national society. Such a sense of community is best achieved when the concept of "nation" is shorn of any connotations of ethnic exclusivity.
Keywords: 330